KOMODIFIKASI PEREMPUAN PADA KONTEN MEDIA SOSIAL ESPORTAINMENT (NETNOGRAFI KRITIS KONTEN OPI ESPORTAINMENT DI MEDIA SOSIAL TIKTOK) - Melitania Pangestuti (2023)
Online games are becoming popular not only in Indonesia but also around the world giving birth to a new culture of "Digital Social Gaming". Women are considered as a minority in game activities, giving rise to a separate stigma and discrimination against women in the virtual game community. Most women or gaming girls are appointed as Brand Ambassadors (BA) in the esports community. The majority of BA online gaming communities vote for women based on their visuals and rely on their bodies and looks to increase the community's popularity. Apart from playing games, the esports community uses social media to introduce their community. One of the social media that is currently popular with the public is Tiktok. There is one esports community that is considered controversial and has a female BA, namely OPI Esports. The esports community actively uploads content on Tiktok, not only providing information about mobile legends games but also following trends that are taking place on Tiktok such as dances that are currently viral. The practical and theoretical objectives of conducting this research include knowing the commodification of women in the Tiktok content of the esports community and describing the views of esport connoisseurs regarding OPI Esports Tiktok content. The method used in this study is qualitative with a netnographic approach and the theory used is the Political Economy of Media by Vincent Mosco. Researchers used four levels of Cyber Media Analysis to analyze data with the results of OPI Esportainment understanding the procedures for using social media Tiktok, interacting with other users and their followers, as well as forming an identity from public opinion that OPI Esportainment is an esports community on a rocking path or can only shake shake. The research results obtained through observation show that BA OPI Esportainment is used as a commodity for the needs of social media content for Tiktok, but what is unfortunate for esports connoisseurs is that OPI Esports does not show its identity as an esports community in its content.